Analysis of Hadiths on Altruism Motivation - Wahid, Abd. (Proceedings of International Conference on Muslim Society and Thought, 2024)
The study of altruism within religious teachings, particularly Hadiths, reveals significant insights into the motivational roots of selflessness. This paper explores the Hadiths related to altruism, emphasizing their role in promoting social cohesion and moral development within Islamic teachings. It underscores the ethical guidance provided by the Hadiths, highlighting their practical applications in fostering altruistic behavior. Previous research has established the foundational role of Hadiths in shaping ethical conduct among Muslims. This study addresses the gap in understanding the specific motivational mechanisms through which these teachings inspire altruism by conducting a comprehensive textual analysis. The research identifies key themes and motivational triggers in the Hadiths, employing a multidisciplinary approach that integrates theology, psychology, and sociology. By elucidating these motivational aspects, the study offers valuable guidance for religious educators, community leaders, and policymakers in promoting altruistic values and behaviors. Ultimately, the exploration of Hadiths on altruism contributes to the ongoing discourse on how religious traditions can inspire and sustain altruistic behavior in the modern world.